The Potential for Waste‐Derived Materials to Form Soil Covers for the Restoration of Mine Tailings in Ireland. (29th December 2015) - Smart, David; Callery, Sean; Courtney, Ronan
Abstract: Revegetation of mine tailings sites can require significant amounts of topsoil, the sourcing of which can be costly and have detrimental impacts. To address this problem at an Irish mine tailings site, engineered soils were created by mixing varying rates of glacial till with stockpiled peat and compost. Soil status was assessed using a range of soil parameters and vegetation growth characteristics and compared with locally sourced topsoil. Hordeum vulgare (Barley) germination and growth trials were assessed on engineered soils: compost with glacial till, peat with glacial till, compost/ peat with glacial till and topsoil. A range of soil quality parameters were examined including: nutrient status, dehydrogenase activity, metals availability and physical characteristics (bulk/particle density and porosity). Results demonstrate that compost derived soils yielded superior plant biomass and nutrient content, whilst peat derived treatments exhibited nutrient deficiency. Whilst the engineered soils offer potential as an alternative to sourcing topsoil for covering mine tailings, the phosphorus and metal content of composts should be assessed prior to inclusion. Copyright © 2015 John Wiley & Sons, Ltd.